Co‐liquefaction of lignite and biomass over Ni7W3 and Ni3W7 catalysts. (11th June 2015) - Yao, Songdong; Du, Yongming; Huang, Feng; Wang, ShaoJun; Wang, Mengmeng
<x xml:space="preserve">Abstract</x> Co‐liquefaction of lignite and biomass was carried out in an autoclave by varying the biomass type and initial hydrogen pressure as well as the catalyst. The properties of the catalysts, raw materials, and residues were characterized by Ultimate analyses, BET, H2‐TPR, TG/DTG, and TPO. The results showed that synergetic effect between lignite and biomass (pine shoot, corn cob, and corn stalk) might be positive, insignificant, or even negative depending on biomass type and reaction conditions. Higher hydrogenation pressure favours the formation of oil and reduction of asphaltene. Catalysts also play important roles in the performance of co‐hydrogenation of lignite and biomass. Highly active catalysts (Ni3W7) may form more active hydrogen species in the solution, stabilizing smaller fragments and increasing the formation of oil.